2015
DOI: 10.1016/j.cej.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a pilot-scale membrane aerated biofilm reactor for the treatment of landfill leachate

Abstract: Please cite this article as: E. Syron, M.J. Semmens, E. Casey, Performance analysis of a pilot-scale membrane aerated biofilm reactor for the treatment of landfill leachate, Chemical Engineering Journal (2015), doi: http://dx. AbstractA 60 litre membrane aerated biofilm reactor (MABR) was successfully employed to treat landfill leachate, which contained very high concentrations of refractory Chemical Oxygen Demand (COD) and ammonium. Air or pure oxygen was supplied to the bioreactor through polydimethyl siloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 28 publications
(31 reference statements)
0
31
0
2
Order By: Relevance
“…MABR for landfill leachate treatment can achieve 80%-99% of nitrification with oxygen transfer rates as high as 35 g O 2 /m 2 -day [73]. When the influent COD/N rate is 5 or higher, the COD, ammonium and total nitrogen removal efficiencies reach 83.7%, 93.1% and 84.6%, respectively [74].…”
Section: Membrane-aerated Biofilm Reactor (Mabr)mentioning
confidence: 91%
“…MABR for landfill leachate treatment can achieve 80%-99% of nitrification with oxygen transfer rates as high as 35 g O 2 /m 2 -day [73]. When the influent COD/N rate is 5 or higher, the COD, ammonium and total nitrogen removal efficiencies reach 83.7%, 93.1% and 84.6%, respectively [74].…”
Section: Membrane-aerated Biofilm Reactor (Mabr)mentioning
confidence: 91%
“…Li et al demonstrated that increasing aeration pressure from 0.005 to 0.03 MPa, led to an increase in the COD:N ratio from 4 to 7 . Similarly, Syron et al observed that when oxygen pressure was increased from 0.015 to 0.02 MPa, complete oxidation to nitrate occurred and the oxygen transfer efficiency was increased from 20% to 80% …”
Section: Membrane Biofilm Reactorsmentioning
confidence: 99%
“…However, MABRs can outperform conventional treatment in terms of energy efficiency and pollutant removal rate due to high oxygen transfer efficiencies and smaller aeration equipment. Operating an MABR with pure oxygen requires up to five times less membrane area compared to operating with air which provides savings in capital investment . Also, Lin et al .…”
Section: Cost Factorsmentioning
confidence: 99%
“…During an investigation, membrane bioreactor system with aeration rate of 35 g O 2 /m 2 /day resulted in 80-83% reduction of COD with initial concentration of 1000 -3000 mg/L [26]. In another study, membrane bioreactor with organic rate of 1.2 g COD/L/day and SRT of 80 days leads to COD and ammonia removal to 63% and 98% with initial concentration of 1550 and 288 mg/L, respectively.…”
Section: Membrane Bioreactor Process Performancementioning
confidence: 99%
“…Partial of 80% removal of nitrogen in aerated Lagoon was done by ammonia evapora- Moving-bed biofilm reactor (MBBR) 800 -2000 20 [24] 7500 -7900 8 [25] Membrane bioreactor (MBR) 1000 -3000 80 -83 [26] 1550 63 [20] 14,000 80 [27] aerobic sequencing batch reactor (ASBR) 4000 87 [21] 3200 30 [28] Aerated lagoons 1740 75 [22] 5518 97 [29] tion [22]. In another study, the use of this method in leachate treatment led to the removal of 97% COD and 92% ammonia nitrogen [29].…”
Section: Aerated Lagoon Process Performancementioning
confidence: 99%